REDDIT QUARANTINED: CONSEQUENCES OF DEALING WITH DISTRUST IN SOCIAL MEDIA PLATFORMS THROUGH RESTRICTING ENGAGEMENT - Copland, Simon (AoIR Selected Papers of Internet Research, 2019)
Online abuse has become a matter of trust for social media platforms, whose role as a facilitator of public debate has been called into question. In response social media companies have become more active in regulating and banning particular users and channels. Through the use of affordances theory, this paper examines one example of the regulation of content on a social media site, the revamp of the quarantining function on Reddit in late 2018. Quarantines are designed to halt participation within and growth of subreddits without banning them outright. The paper uses quantitative and qualitative data to examine the consequences of this revamp on two subreddits, r/Braincels and r/TheRedPill. Through studying activity levels on these subreddits the paper argues that quarantines did limit discussion within these subreddits. However, it also argues that the revamp had unintended consequences, in particular a growth in distrust between subreddit users and Reddit as a site, and a shift of users away from Reddit to less regulated sites. The paper argues that quarantining shifted the affordances of Reddit, in this instance resulting in greater discouragement of activity on particular subreddits. Using the mechanisms and conditions framework (Davis and Chouinard, 2016) the paper however argues that users adapted to and circumvented this discouragement to continue engaging in particular behavior. While quarantining had short term benefits, using an affordances framework this paper argues it had unintended consequences, ones which can result in a continued radicalization of actions and beliefs, furthering distrust in the online sphere.